Exploring Students’ Perceptions Towards 21st Century Skills Through Novel Applications: A Comparative Study among EFL Learners in Iraq - Bilgin, Recep (Arab world English journal, 2024)
Many initiatives have been seized to integrate 21st-century skills into the curriculum. They encompass specific competencies under five areas, which are vital subjects, 21st-century themes, innovation, career, and literacy skills. Accordingly, the present qualitative study was carried out at Tishk International University in Erbil, Iraq on 50 first-year students, aged between 18 and 23 in 10 departments through semi-structured interviews, according to the principles of phenomenological research design in the fall semester of the 2023-2024 academic year. This study aimed to explore the attitudes of tertiary-level students toward 21st-century skills through the lens of practical reflections on their social, personal, and academic lives. Specifically, it aimed to address the following question: What 21st-century skills are more significant than others? The rationale for exploring university students’ perceptions of 21st-century skills and their practical applications was that students seemed perplexed regarding the significance of practical reflections in the Iraq context. Collected data were transcribed by the Go Transcribe application and classified based on the principles of content analysis. The findings revealed that reading, productivity, accountability, creativity, technology, and financial literacy were prioritized in each category by the participants, and they had novel ways to develop them regularly. The findings of this study can shed light on some points about the implementation of 21st-century skills with clear-cut strategies at educational institutions.